Evaluation of Urumiyeh (Iran) City Park in Terms of Noise Analysis and Sound Landscape - Serkan Özer; Nazli Esmaeili Hesar; Elif Önal (Research in Agricultural Sciences)
This study was conducted to evaluate how sound affects the soundscape character of Urumiyeh City Park in Urumiyeh, Iran, as a design and planning element. The study includes determining the sound status of the park and determining to what extent the noise factor, if any, can affect the soundscape. In the study method, first, the existing sound sources of the park were determined in the field. Then, for noise measurements, the study area was divided by 50 m equal intervals and 80 stations were determined. Measurements were made at these stations in three different time periods, Tuesday, Friday, and Saturday, in the afternoon, mid-afternoon and evening, for two months. As a result of the measurements, it has been determined that it exceeds 45 dB(A), which is given as the acceptable noise value for parks by WHO, in the entire park, and it exceeds it to a great extent, approximately 42 dB(A) at some measurement stations. In the evaluation of the obtained sound data, 10 different noise maps were made using the Kriging method on the ArcGis10.6. program. Finally, suggestions were made by discussing how to highlight the desired sounds in the park to reduce the noise that bothers people in Urumiyeh City Park, using concave elements and walls to reflect positive sounds and taking other necessary measures.